Modelling the morphology and thermomechanical behaviour of low-bandgap conjugated polymers and bulk heterojunction films. Issue 2 (13th January 2017) - Root, Samuel E.; Jackson, Nicholas E.; Savagatrup, Suchol; Arya, Gaurav; Lipomi, Darren J.
Abstract : Schematic diagram showing the information flow from molecular structure, to atomistic model, to a slice of the solid morphology under mechanical deformation and the stress–strain response. Abstract : This paper describes the use of molecular dynamics (MD) to predict the nanoscale morphology and thermomechanical behavior of three low-bandgap semiconducting polymers and their blends with PC71 BM. While the three polymers modeled in this study—PTB7, PDTSTPD, and TQ1—all exhibit the donor–acceptor motif characteristic of high-performance donor materials in organic solar cells, they exemplify different morphologies in the solid state. Predictions from the atomistic simulations presented here include the average conjugation length of the polymers, the structural arrangement of conjugated donor and acceptor units in neat and bulk heterojunction (BHJ) films, as well as the glass transition temperature and tensile modulus of neat and BHJ polymer films. Calculated tangent correlation functions exhibit oscillatory decay. This finding suggests that DA polymers are more appropriately modeled as ribbon-like chains as opposed to worm-like chains. To account for the range of morphologies accessible by processing manipulations, both a melt-quenched and a self-aggregated morphology are prepared. Owing to the greater free volume of the self-aggregated morphology, these solid structures are found to be softer and weaker than the melt-quenched morphologies. The experimental modulus measured previously for PDTSTPD is similar to the predicted self-aggregated morphology, while the experimental modulus of PTB7 is similar to the predicted melt-quenched modulus. Our comparisons with experiment suggest that solution-processing plays a critical role in optimizing the mechanical properties of conjugated polymeric materials. Overall, the results of this study suggest the promise of MD simulations in determining the ways in which molecular structure influences the morphology and mechanical properties of bulk heterojunction films for solar cells and other organic electronic devices.